Do hedge funds manage their reported returns? - Vikas Agarwal; Naveen D. Daniel; Narayan Y. Naik (University of Cologne, Centre for Financial Research (CFR), 2009)
For funds with greater incentives and greater opportunities to inflate returns, we find that (i) returns during December are significantly higher than those during the rest of the year even after controlling for risk in both time-series and the cross-section; (ii) this December spike is greater than that for funds with lower incentives and opportunities to inflate returns. These results suggest that hedge funds manage their returns upwards in an opportunistic fashion in order to earn higher fees. Finally, we provide strong evidence that funds inflate December returns by under-reporting returns earlier in the year but only weak evidence that funds borrow from January returns in the following year.
Keywords: 330